2019
DOI: 10.1111/pedi.12963
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover markers during the remission phase in children and adolescents with type 1 diabetes

Abstract: Background and aim: In rodents, osteocalcin (OCN) stimulates insulin production and insulin sensitivity, both important factors during partial remission in humans with type 1 diabetes (T1D). However, decreased OCN has been reported in both adult and pediatric T1D. This study aims at investigating bone turnover and partial remission in children and adolescents with recent onset T1D.Subjects and methods: Ninety-nine individuals (33% girls) were recruited within 3 months of T1D onset and examined three times, 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…They had a total of 3 visits with 6 months apart. In‐ and exclusion criteria have been described previously 15 . Eighty‐two participants were included in the original cohort.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They had a total of 3 visits with 6 months apart. In‐ and exclusion criteria have been described previously 15 . Eighty‐two participants were included in the original cohort.…”
Section: Methodsmentioning
confidence: 99%
“…14 A previous study from our research group found an association between the bone marker C-terminal crosslinked telopeptide of type 1 collagen (CTX) and IDAA 1c in the partial remission phase and hypothesized a mechanism related to improved IS. 15 However, the research in this field is still limited.…”
Section: The Partial Remission Phasementioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 99 pediatric patients recently diagnosed with T1D, BMD was unchanged over the first year after diagnosis [42]. Interestingly though, osteocalcin and P1NP (bone formation markers) decreased, while CTX (bone resorption marker) increased during the same period, revealing that bone turnover disturbances are present since very early stages of the disease.…”
Section: When Do Bone Effects Of T1d Become Manifest?mentioning
confidence: 99%